Abdominal and gluteo-femoral markers of adiposity and risk of vascular-metabolic mortality in a prospective study of 150 000 Mexican adults. (9th March 2021) - Gnatiuc, Louisa; Tapia-Conyer, Roberto; Wade, Rachel; Ramirez-Reyes, Raúl; Aguilar-Ramirez, Diego; Herrington, William; Hill, Michael; Lewington, Sarah; Torres, Jason; Trichia, Eirini; Collins, Rory; Peto, Richard; et al.
Abstract: Aims: Results of previous studies of abdominal adiposity and risk of vascular-metabolic mortality in Hispanic populations have been conflicting. We report results from a large prospective study of Mexican adults with high levels of abdominal adiposity. Methods and results: A total of 159 755 adults aged ≥35 years from Mexico City were enrolled in a prospective study and followed for 16 years. Cox regression, adjusted for confounders, yielded mortality rate ratios (RRs) associated with three markers of abdominal adiposity (waist circumference, waist–hip ratio, and waist–height ratio) and one marker of gluteo-femoral adiposity (hip circumference) for cause-specific mortality before age 75 years. To reduce reverse causality, deaths in the first 5 years of follow-up and participants with diabetes or other prior chronic disease were excluded. Among 113 163 participants without prior disease and aged 35–74 years at recruitment, all adiposity markers were positively associated with vascular-metabolic mortality. Comparing the top versus bottom tenth of the sex-specific distributions, the vascular-metabolic mortality RRs at ages 40–74 years were 2.32 [95% confidence interval (CI) 1.84–2.94] for waist circumference, 2.22 (1.71–2.88) for the waist–hip ratio, 2.63 (2.06–3.36) for the waist–height ratio, and 1.58 (1.29–1.93) for hip circumference. The RRs corresponding to each standard deviation (SD) higher usual levels of these adiposity markers were 1.34 (95% CI 1.27–1.41), 1.31 (1.23–1.39), 1.38 (1.31–1.45), and 1.18 (1.13–1.24), respectively. For the markers of abdominal adiposity, the RRs did not change much after further adjustment for other adiposity markers, but for hip circumference the association was reversed; given body mass index and waist circumference, the RR for vascular-metabolic mortality for each one SD higher usual hip circumference was 0.80 (0.75–0.86). Conclusions: In this study of Mexican adults, abdominal adiposity (and in particular the waist–height ratio) was strongly and positively associated with vascular-metabolic mortality. For a given amount of general and abdominal adiposity, however, higher hip circumference was associated with lower vascular-metabolic mortality.